Impact of Consumer’s Attitude towards Social Media Influencers on Purchase Intention (Journal of Informatics Education and Research, 2025)
Understanding influencer marketing is the necessity of the hour. The dimensions of influencer are nearby grown thrice since 2019. The dimension of influencer marketing in India stood at 55 billion Indian rupees with yearly growth rate of 20%. The prediction as per statista states that by the year 2027 , influencer marketing size to be near to approximately 107 billion Indian rupees. There is rise in number of studies on this topic as the dimension is continuously expanding. Present study examines the role of attitude of consumer toward social media influencer’s on consumer purchase intention and brand attitude. It also intends to determine the impact of attitudes of consumer toward SMI on purchase intentions. Collection of data is done from 600 respondents from North India. Subsequent to the data collection, it is examined using the technique of factor analysis by applying CFA, EFA and SEM. This study illustrates positive impact of consumer’s attitude towards Social media influencer’s on consumer purchase intention. It has been found that attitude of consumer towards social media influencers significantly affect the purchase intentions of consumers. The findings of study help advertisers and marketers in the industry to know how influencer marketing helps consumer purchase intention. They also allow marketers to know the attitude of consumers toward SMI and therefore better choose influencers capable of making purchase intentions among existing and potential customers.